Nutrition Adequacy Level and Stunting in Children Aged 48‒59 Months in the Coastal Area of Kendari City, Indonesia - Jufri, Nurnashriana; Marliyati, Sri Anna; Anwar, Faisal; Ekayanti, Ikeu (Jurnal Gizi dan Pangan, 2023)
This study aims to explore the relationship between nutritional adequacy and height-for-age z-scores (HAZ) in toddlers in Kendari City's coastal region. This cross-sectional analysis involved 96 children aged 48‒59 months. Height measurements was converted to HAZ, while a 24-hour dietary recall was conducted to assess nutritional intake. Data were analyzed using Pearson product moment test and multiple linear regressions. The study revealed a significant HAZ correlation with calcium, iron, and copper adequacy levels (p<0.05). Notably, in Kendari City's coastal area, stunting is found in toddlers aged 48‒59 months due to nutritional inadequacy.